Malaria in children in Peru: magnitude and some demographic and socioeconomic characteristics, 2010-2023 - Arrasco Alegre, Juan Carlos (2025)
Introduction: Malaria is one of the most important parasitic diseases in humans, and children are the vulnerable group with the highest risk of complications and death. Objective: To analyze the magnitude of the incidence of malaria in children and its relationship with some demographic and socioeconomic characteristics. Materials and methods: Cross-sectional, descriptive, ecological study, analyzing secondary sources; district and national analysis units, study period 2010-2023. Results: In Peru, in the period 2010-2023, 219,126 cases of malaria in children were reported, representing 41.64% of the national total and an average annual incidence rate (AAR) of 12.07 cases/1000 children. The TIAM in <5 years was 12.40 cases/1000, the highest TIAM between 2010-2019 and the lowest between 2020-2021, Loreto reported 89.62% of cases with the highest TIAM (49.19 cases/1000) in this group. P. falciparum caused the highest average annual mortality and fatality rates. The weekly trend shows differentiated behavior by macroregions. The highest TIAM corresponded to: male children (12.33/1000), from group 1 to <5 years (14.09/1000), from the jungle region (17.17/1000), from districts of the quintile with the highest: overcrowded housing (28.68/1000), housing without sanitary services (61.04/1000), at least one Unsatisfied Basic Need (30.66/1000), homes with high economic dependence (27.24/1000), homes with children who do not attend school (20.26/1000), lower human development index (53.61/1000) Conclusions: In Peru, children have a higher risk of morbidity and mortality compared to other groups, the highest TIAM correspond to districts located in the jungle region, at a lower altitude and lower population density, lower human development index and higher unmet basic needs.